The Use of Modern Technologies to Increase the Level of Trust in Society - Denis A. Gromyko (RUDN Journal of Public Administration, 2023)
One of the pressing issues of the modern world is the problem of trust in government. The election process is a pivotal event in society’s life, influencing a country’s future. Decreased trust in authority, including elections, leads to vulnerability in the voting and result tallying process. Simultaneously, the rapid advancement of information technology, automation, and computerization affecting almost all spheres of life, among other things, has a widespread impact on the functioning of government institutions. One of the key tasks addressed by new technologies is increasing trust levels in society. Blockchain technology, or distributed ledgers, has revolutionized the world of information technology and found applications in various domains, including the organization of elections at different levels. The use of blockchain technology in the electoral process can help address the trust issue by ensuring transparency, reliability, and confidentiality in voting, while minimizing the possibility of result tampering. In a blockchain-based system, voting can occur anonymously without intermediaries and intermediate technologies. This article examines the problem of trust in government institutions, highlights issues in the electoral process, presents a description of the blockchain technology-based solution, and provides examples of existing systems used during the electoral process. It concludes that the implementation of blockchain technology in the electoral process will ensure a more transparent and secure voting process, significantly increasing trust in authority.